Metabolism of oral trefoil factor 2 (TFF2) and the effect of oral and parenteral TFF2 on gastric and duodenal ulcer healing in the rat. Issue 4 (1st October 1999) - Poulsen, S S; Thulesen, J; Christensen, L; Nexø, E; Thim, L
Abstract : BACKGROUND: Trefoil factors (TFFs) are peptides produced by mucus-secreting cells in the gastrointestinal tract. A functional association between these peptides and mucus, leading to stabilisation of the viscoelastic gel overlying the epithelia, has been suggested. Both oral and parenteral administration of the peptides increase the resistance of the gastric mucosa. AIM: To study the effect in rats of oral and parenteral porcine trefoil factor 2 (pTFF2) on the healing of gastric and duodenal ulcerations and to clarify the distribution and metabolism of orally administered pTFF2 in the gastrointestinal tract. METHODS: Gastric ulcers were induced in female Sprague-Dawley rats by indomethacin and duodenal ulcers by mercaptamine. The rats were treated for up to seven days with oral or subcutaneous pTFF2. Ulcer size after treatment was assessed by stereomicroscopy after whole mount staining with periodic acid-Schiff stain. 125 I-labelled pTFF2 was given orally to rats, and tissues were investigated by gamma counting of samples and by autoradiography of paraffin embedded sections. RESULTS: pTFF2 accelerated gastric ulcer healing after both oral and subcutaneous administration. Duodenal ulcers were aggravated by both treatments. After oral administration of 125 I-pTFF2, intact peptide was recovered from the superficial part of the mucus layer in the stomach; it passed through the small intestine but was degraded in the caecum. Only a minor part of the labelled pTFF2 entered the colon and was excreted in the faeces. Most of the label was excreted in the urine. CONCLUSIONS: Oral as well as parenteral pTFF2 accelerates the healing of gastric ulceration and aggravates duodenal ulcers. Oral pTFF2 binds to the mucus layer of the stomach and the small intestine but does not reach the colonic mucosa.